Managing Benign and Malignant Oral Lesions with Carbon Dioxide Laser: Indications, Techniques, and Outcomes for Outpatient Surgery - Saibene, Alberto Maria; Rosso, Cecilia; Castellarin, Paolo; Vultaggio, Federica; Pipolo, Carlotta; Maccari, Alberto; Ferrari, Daris; Abati, Silvio; Felisati, Giovanni (The Surgery Journal, 2019)
Purpose Because of its affinity for water-based tissues, carbon dioxide (CO2) laser has become an instrument of choice for treating oral mucosa conditions, ranging from inflammatory to malignant lesions. The aim of this work is to systematically evaluate the outcomes of laser surgery over a wide range of lesions, while providing a solid and reproducible protocol for CO2 laser surgery in the outpatient management of oral lesion.Methods Seventy-eight patients underwent 92 laser outpatient procedures for treatment of a wide range of benign and malignant lesions. We performed 60 removals, 11 exeretic biopsies, 15 vaporizations, and 3 vaporization/removal combined. We analyzed laser parameters applied for each technique and provided a systematic evaluation of surgical results.Results No problems occurred intraoperatively in any of the patients. Five patients complained marginal pain, while 3 patients had postsurgery bleeding. All treatments were successful, with the notable exception of 3 relapsing verrucous proliferative leukoplakias and an infiltrating squamous cell carcinoma of the tongue requiring radicalization. We did not record any adverse reactions to drugs or lesions due to laser action. Concordance between clinical diagnosis and pathology results was at 94.8%.Conclusions Our data indicate that CO2 laser is a solid choice for outpatient treatment of oral lesions. This technique grants painless and almost bloodless treatment, with negligible recurrence rates. Providing a solid reference for laser settings and operative techniques could provide a foundation for further exploring this tool while offering the basis for a positive comparison between different surgical techniques and options.
Keywords: laser surgery; oral lesions; CO2; leukoplakia; benign oral lesions; outpatient procedures